Lactone-Based Liquid Electrolytes for Fluoride Shuttle Batteries. Issue 1 (21st January 2021) - Kawasaki, Mitsuo; Morigaki, Ken-Ichi; Kano, Gentaro; Nakamoto, Hirofumi; Takekawa, Reiji; Kawamura, Junichi; Minato, Taketoshi; Abe, Takeshi; Ogumi, Zempachi
Abstract : Rechargeable secondary batteries operating through fluoride-ion shuttling between the positive and negative electrodes, referred to as fluoride shuttle batteries (FSBs), offer a potentially promising solution to overcoming the energy-density limitations of current lithium-ion battery systems. However, there are many technical issues that need to be resolved to achieve high-quality fluoride-carrying electrolytes and ensure reversible transformations between a metal and its fluoride counterpart at both electrodes. Here, we introduce novel lactone-based liquid electrolytes consisting either of CsF or KF, which are prepared by a solvent substitution method. Although the maximum fluoride-ion concentration achieved by the method is approximately 0.05 M, these systems behave as strong electrolytes where CsF(KF) is almost fully dissociated into Cs + (K + ) and F − ions to give a maximum ionic conductivity of 0.8 mS.cm −1 . Hence, the solvent supports electrochemically active fluoride ions that can drive reversible metal/metal-fluoride transformations at room temperature for a wide range of metal electrodes. However, irreversible reductive reactions of the solvent, also promoted by the fluoride ions, limit currently the negative potential window to approximately −1.5 V vs the standard hydrogen electrode.